Impact of the wetting layer thickness on the emission wavelength of direct band gap GeSn/Ge quantum dots. (19th July 2017) - Ilahi, Bouraoui; Al-Saigh, Reem; Salem, Bassem
Abstract: The effects of the wetting layer thickness ( t WL ) on the electronic properties of direct band gap type-I strained dome shaped Ge(1− x ) Sn x quantum dot (QD) embedded in Ge matrix is numerically studied. The emission wavelength and the energy difference between S and P electron levels have been evaluated as a function of t WL for different QD size and composition with constant height to diameter ratio. The emission wavelength is found to be red shifted by increasing the wetting layer thickness, with smaller size QD being more sensitive to the variation of t WL . Furthermore, the minimum Sn composition required to fit the directness criteria is found to reduce by increasing the wetting layer thickness.